Frank Exline, ed., The Code of Colorado Springs: Comprising Article XX of the Constitution of the State of Colorado, the Charter, Amendments Thereto, and General Ordinances of the City of Colorado Springs, Colorado, 1914 (Colorado Springs, CO: the Joslyn Quick Printery, 1914), 273. Chapter 6—Of Public Offenses and Penalties, Article 1—Offenses Concerning the Public Peace, § 501— Carrying Concealed Weapons. - (:unkn) unknown (General Publisher, 1914)
Prohibited the concealed carry of any pistol, revolver, Bowie-knife, dirk, or other deadly weapon. Prohibited the display or floush of any deadly weapon in a threatening or boisterous manner.
--
Keywords: CARRY - CONCEALED